RANCANG BANGUN ALAT PEMBERSIH DAN PENYORTIR TELUR BERBASIS ARDUINO UNO - Pratama, Indra; Rezki Imanda; Febriansyah, Aan; Muharani, Laily (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
The problem raised in making this final project was that there were still many dirty and rotten eggs being sold in local shops. So, the author's goal in making this final project is to be able to clean eggs, sort the bad and good eggs, and count the total eggs, the number of bad and good eggs. The method used uses 3 rotating brushes to clean eggs, an LDR sensor to detect egg quality, a servo motor for egg sorting, an IR sensor to count eggs and displayed on a LCD 20x4 I2C. The results of testing the IR sensor with 5 trials obtained the lowest detection accuracy, namely 95%, while the LCD 20x4 I2C can display information on total eggs, number of rotten and good eggs. The LDR sensor can differentiate the ADC value range for good eggs, which is around 630 - 660, while the ADC value range for bad eggs is more than 700 - 720. However, the cleaning system using a rotating brush shows that the brush is not able to clean all dirt optimally.